2017
DOI: 10.1080/13813455.2017.1309052
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of adipose triglyceride lipase decreases arachidonic acid release and prostacyclin secretion in human aortic endothelial cells

Abstract: Background: Vascular endothelial cells represent an important source of arachidonic acid (AA)-derived mediators involved in the generation of anti- or proatherogenic environments. Evidence emerged (in mast cells), that in addition to phospholipases, neutral lipid hydrolases as adipose triglyceride lipase (ATGL) also participate in this process. Objective: To examine the impact of ATGL on AA-release from cellular phospholipids (PL) and on prostacyclin secretion in human aortic endothelial cells (HAEC). Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…Recent evidence has suggested that TAG lipolysis mediated by ATGL contributes to the production of lipid mediators in endothelial and immune cells (Dichlberger et al , 2014; Schlager et al , 2015; Riederer et al , 2017). Here we asked whether lipid droplet breakdown via ATGL is required for lipid mediator production in serum-starved cancer cells, and whether it mediates hGX-sPLA 2 -stimulated PGE 2 synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has suggested that TAG lipolysis mediated by ATGL contributes to the production of lipid mediators in endothelial and immune cells (Dichlberger et al , 2014; Schlager et al , 2015; Riederer et al , 2017). Here we asked whether lipid droplet breakdown via ATGL is required for lipid mediator production in serum-starved cancer cells, and whether it mediates hGX-sPLA 2 -stimulated PGE 2 synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In immune and cancer cells, LDs have long been implicated in AA storage, trafficking and eicosanoid production (Dvorak et al , 1983; Triggiani et al , 1994; Bozza et al , 2011). It was only recently shown that ATGL provides precursors for lipid mediator production and modulates neutrophil immune responses in vivo (Dichlberger et al , 2014; Schlager et al , 2015; Riederer et al , 2017). However, it is not yet clear how LDs manage PUFA trafficking for lipid mediator production in mammalian cells and how they cooperate with the canonical PLA 2 -mediated pathways (Guijas et al , 2014; Jarc & Petan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Patients with high ARA levels at baseline showed a 54% increased probability of requiring surgical repair during follow-up. Previous research concentrated on aortic endothelial cells and aortic smooth muscle cells [ 62 , 63 ]. Despite the focus on aortic cells, there are very few studies about aortic dissection or aneurysm.…”
Section: Discussionmentioning
confidence: 99%
“…ATGL-deficient mice present severe micro- and macrovascular endothelial dysfunction [ 69 ], including impairment of vasodilatory, and reduction of eNOS/cGMP signaling. In human aortic endothelial cells (HAEC), silencing ATGL decreased the efficiency of stimulus-induced arachidonic acid (AA) release and prostacyclin secretion [ 70 ]. Adipose tissue microvascular endothelial cells (aMVECs) ATGL, but not HSL, plays an essential role in regulating adipose tissue lipid uptake through secreting PPARγ ligands [ 71 ].…”
Section: Endothelial Cell Metabolismmentioning
confidence: 99%